Clinical effect of CGF blood concentration factor in extracting supernumerary teeth in the middle and high positions of the upper palate - Bing Yuan; Chunyan He; Weidong Lai (SLAS Technology)
Objective: this article aims to compare the postoperative clinical effects and analysis of using patient’s autologous blood extracted CGF (concentrated growth factors) blood concentration factor to fill the extraction wound of supernumerary teeth (ST) in patients with maxillary palatal type III high buried supernumerary teeth. Methods: 108 patients (a total of 173 supernumerary teeth) with maxillary palatal bone buried supernumerary teeth who visited the Department of Stomatology at Handan Stomatological Hospital from September 2022 to September 2024 were selected as the study subjects. Preoperative images were taken for curved surface tomography and CBCT (Cone Beam Computed Tomography) diagnosis. By analyzing the sample population for clinical classification, 60 patients (a total of 94 supernumerary teeth) who met the inclusion criteria were randomly divided into two groups and underwent minimally invasive surgery under general anesthesia to remove supernumerary teeth. The experimental group used autologous blood to extract CGF blood concentration factor through a blood centrifuge to fill the extraction socket wound, while the control group did not use it. The postoperative infection, pain level, swelling degree, wound healing after suture removal were observed in both groups of patients, as well as the comparison of alveolar bone recovery and bone density changes between CBCT taken after surgery and follow-up 3 months later. Results: infection situation: after the extraction of type III high buried supernumerary teeth on the maxillary palatal side, there were no cases of infection in the experimental group and the control group after surgery, and there was no statistically significant difference (P > 0.05). Postoperative pain level: after the extraction of type III buried supernumerary teeth on the maxillary palatal side, the pain level in the control group was higher than that in the experimental group on days 1, 2, and 3 after surgery (P < 0.05), while there was no statistically significant difference in pain level between the two groups on days 5 and 7 after surgery (P > 0.05). Degree of postoperative swelling: on postoperative days 1, 2 and 3, the degree of swelling in the control group was significantly higher than that of the experimental group (P < 0.05), but on postoperative days 5 and 7, the degree of swelling in the two groups was comparable, with no significant difference (P > 0.05). Wound healing: when the stitches were removed on the 7th postoperative day, all the wounds in the experimental group reached II-A healing; 2 cases in the control group were II-B, and the rest were II-A. The healing situation of the experimental group was better, but the statistical difference was not significant (P > 0.05). Maxillary alveolar bone recovery and bone density change value: immediate postoperative CBCT showed no significant difference in bone density between the two groups. However, at the 3-month postoperative follow-up, the bone density of the experimental group was significantly better than that of the control group (P < 0.05). Conclusions: after minimally invasive extraction of type III high buried supernumerary teeth on the maxillary palate, the wounds of the CGF experimental group and the control group were not infected, and there was no significant difference. After the extraction of type III high buried supernumerary teeth on the maxillary palatal side, the CGF experimental group showed better postoperative pain, swelling, and wound healing levels than the control group. The results of CBCT examination after the extraction of type III high buried supernumerary teeth on the maxillary palatal side showed no significant difference in bone density between the two groups. However, during the follow-up CBCT examination at 3 months after surgery, the bone recovery and bone density of the CGF experimental group were better than those of the control group.